Characterization of human pyruvate dehydrogenase kinase isoform 2 (PDHK2 - Hu, Liangyan (Kansas State University, 2008)
Specific mutants were developed to evaluate the roles of several residues in [Alpha]8 helix of the regulatory (R) domain of human pyruvate dehydrogenase kinase 2 (PDHK2) in the linkage between the Regulatory (R) and catalytic (Cat) domain (Q144A), dichloroacetate (DCA)/pyruvate inhibition (R154C, R158A, I157F) and stimulation by reductive acetylation (L160A, R154C/L160A). All mutants, with the exception of L160A, were active, and were bound to and had their activities enhanced by dihydrolipoyl acetyltransferase (E2). The cross arms between subunits are anchored by W383. Based on the studies on the W383F mutant, W383 provided majority of the intrinsic Trp fluorescence; and ligand(s) binding quenched primarily (pyruvate) or exclusively (ADP or ATP) the fluorescence of W383. The Q144 mutation in the R domain caused 14-fold weaker K[superscript]+ binding with ATP in the Cat domain but did not alter the weaker K[superscript]+ binding with ADP unless Pi was included. Similarly, with 100 mM K[superscript]+, the Q144A mutant had weaker ATP binding but the affinity for ADP was not changed even in the presence of Pi, which enhanced the binding of ADP to kinase by 2-fold. R154 and R158 were shown to be important residues in the inhibition by pyruvate, DCA and Cl[superscript]-. The R154C, R154C/L160A and R158A mutations reduced the inhibition by DCA or pyruvate using E1 or E1[dot in middle of line]E2 as the substrates. Pyruvate plus ADP did not significantly hinder the binding of GST-L2 to these mutants in AUC studies. Cl[superscript]- appears to bind to kinase at the same site as DCA/pyruvate based on lack of Cl[superscript]- effects with above mutants and evidence that Cl[superscript]- weakened the inhibition by DCA or pyruvate of native PDHK2. Q144 and L160 may play important roles in the signal transmission from the lipoyl group-binding site to the active site. Q144A and R154C/L160A mutants were less stimulated by reductive acetylation than other mutants and native PDHK2. Nov3r binds to where lipoyl goup binds PDHK2. Using E1 alone as substrate, Nov3r binding caused a 20% increase of kinase activity at low levels. Nov3r binding also reduced the inhibition of DCA/pyruvate with elevated K[superscript]+ plus Pi.
Keywords: PDHK2; Chemistry, Biochemistry (0487)